2000
DOI: 10.1002/(sici)1097-0134(20000515)39:3<204::aid-prot20>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of yeast phosphoglycerate kinase into amyloid-like structure

Abstract: Yeast phosphoglycerate kinase is a structurally well-characterized enzyme consisting of 415 amino acids without disulfide bonds. Anion-induced refolding from its acid-unfolded state gives rise to the formation of worm-like amyloid fibrils with a persistence length of 73 nm. Electron microscopy and small-angle X-ray scattering data indicate that the fibrils have an elliptical cross-section with dimensions of 10.2 nm x 5.1 nm. About half of all amino acids are organized in form of cross-beta structure which give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 30 publications
(50 reference statements)
6
49
0
Order By: Relevance
“…The results together with the outcome of far-UV circular dichroism measurements support the conclusion that ␤ 2 m in 40 -50% acetonitrile and 25-35% TFE forms a partially structured intermediate or a distinctly different conformation that binds CR more strongly than the native form and precipitates out of solution over time. Transient intermediates of proteins with less ␤-structure and more ␣-helix have also been found in other studies of amyloid disease-related and unrelated proteins (10,36,37,42), and it has been suggested that a defined ␣-helix content in partially structured intermediates may favor the further transition to ␤-sheets and amyloid fibrillation (39,43).…”
Section: Conformational Variant Of ␤ 2 M Has An Increased Binding Affsupporting
confidence: 57%
See 1 more Smart Citation
“…The results together with the outcome of far-UV circular dichroism measurements support the conclusion that ␤ 2 m in 40 -50% acetonitrile and 25-35% TFE forms a partially structured intermediate or a distinctly different conformation that binds CR more strongly than the native form and precipitates out of solution over time. Transient intermediates of proteins with less ␤-structure and more ␣-helix have also been found in other studies of amyloid disease-related and unrelated proteins (10,36,37,42), and it has been suggested that a defined ␣-helix content in partially structured intermediates may favor the further transition to ␤-sheets and amyloid fibrillation (39,43).…”
Section: Conformational Variant Of ␤ 2 M Has An Increased Binding Affsupporting
confidence: 57%
“…In a number of cases, amyloid fibril formation from these disease-associated proteins has been shown to be initiated in vitro under conditions that stabilize partially unfolded soluble intermediates of the native proteins (3,5,6,35,36). A growing list of additional proteins and peptides, including de novo designed synthetic proteins without known amyloid disease association, may also form amyloid fibrils in vitro under similar conditions (10,12,13,37,38). Amyloid fibrils consist of stable and insoluble assemblies of proteins in stacked ␤-sheets (39).…”
Section: Conformational Variant Of ␤ 2 M Has An Increased Binding Affmentioning
confidence: 99%
“…Fig. 4 compares parameters of far-ultraviolet (UV) circular dichroism (CD) spectra measured for 'pure' amyloidogenic conformations of 11 proteins (SH3 domain [98], cytocrome c 552 [110], monellin [100], methionine aminopeptidase [106], SMA [138], a-lactalbumin [115], phosphoglycerate kinase, PGK [105], amylin [93], prothymosin a [114], Ab [151] and a-synuclein [97]), with those retrieved for the four basic protein conformations, native, molten globule, premolten globule and unfolded states. In this plot data for the premolten globule and unfolded states are taken from [11], and the data for molten globules are from [154].…”
Section: Fibrillogenesis Of Natively Unfolded Proteins; Requirement Fmentioning
confidence: 99%
“…Electron microscopy shows that the fibrils are straight and unbranched and are 40 -120 Å in diameter (9,10). Also proteins not known to be associated with amyloid disease may form amyloid fibrils under in vitro conditions that favor partially folded states (11)(12)(13)(14)(15). These states are more prone to aggregation than the native state because hydrophobic residues, which are largely buried within the core of the native protein, become more exposed upon partial unfolding.…”
mentioning
confidence: 99%